PENGARUH STRATEGIC LEADERSHIP TERHADAP COMPETITIVE POSITIONING MELALUI INTELLECTUAL CAPITAL TERHADAP PERUSAHAAN MANUFAKTUR - Martin, Kurniawan (Business Accounting Review, 2015)
This study aimed to analyze the influence of strategic leadership to the competitive positioning through intellectual capital. The independent variables used in this study was strategic leadershipÂ  measured by six indicators, intervening variables used was intellectual capital and the dependent variable used was competitive positioning measured by using the five force.samples used in this study were 60 managers working in a manufacturing companies in Surabaya. This research took the most answers that were 30 people manager. The analysis technique used was Partial Least Square (PLS).The results showed that there was a positive correlation on the strategic leadership to competitive positioning, positive influence of strategic leadership to intellectual capital, and positive influence of intellectual capital to competitive positioning.